Effects of Weight-Bearing on Tibiofemoral, Patellofemoral, and Patellar Tendon Kinematics in Older Adults - Kefala, Vasiliki; Ali, Azhar A.; Hamilton, Landon D.; Mannen, Erin M.; Shelburne, Kevin B. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Quantification of natural knee kinematics is essential for the assessment of joint function in the diagnosis of pathologies. Combined measurements of tibiofemoral and patellofemoral joint kinematics are necessary because knee pathologies, such as progression of osteoarthritis and patellar instability, frequently concern both articulations. Combined measurement of tibiofemoral and patellofemoral kinematics also enables calculation of important quantities, specifically patellar tendon angle, which partly determines the loading vector at the tibiofemoral joint, and patellar tendon moment arm. The goals of this research were measurement of the differences in tibiofemoral and patellofemoral kinematics, patellar tendon angle (PTA), and patellar tendon moment arm (PTMA) that occur during non-weightbearing and weightbearing activities in older adults. Methods: High-speed stereo radiography was used to measure the kinematics of the tibiofemoral and patellofemoral joints in subjects as they performed seated, non-weightbearing knee extension and two weightbearing activities: lunge and chair rise. PTA and PTMA were extracted from the subject’s patellofemoral and tibiofemoral kinematics. Kinematics and the root mean square difference between non-weightbearing and weightbearing activities were compared across subjects and activities. Results: Internal rotation increased with weightbearing (mean RMSD from knee extension was 4.2˚± 2.4˚ for lunge and 3.6 ± 1.8˚ for chair rise) and anterior translation was also greater (mean RMSD from knee extension was 2.2 ± 1.2 mm for lunge and 2.3 ± 1.4 mm for chair rise). Patellar tilt and medial-lateral translation changed from non-weightbearing to weightbearing. Changes of the patellar tendon from non-weightbearing to weightbearing were significant only for PTMA. Conclusions: While weightbearing elicited changes in knee kinematics, in most degrees-of-freedoms these differences were exceeded by intersubject differences. These results provide comparative kinematics for the evaluation of knee pathology and treatment in older adults.